Os desafios da implementação das contratações públicas inovadoras no âmbito do Ministério da Saúde - Pereira, Francisco Dennes Rocha (2024)
This research examines the key challenges faced by the Ministry of Health in implementing innovative public procurement. It outlines the legal framework governing such procurement in Brazil, analyzes the processes for acquiring innovative products and services at the Ministry, and offers recommendations for improving innovation procurement practices. The research adopts a case study design of the Ministry of Health, utilizing a mixed-method approach. Data collection methods include document analysis and semi-structured interviews, with content analysis performed using Atlas.ti software. Preliminary findings reveal the existence of 16 normative acts directly related to innovative public procurement. The analysis of contracts and administrative processes shows that the use of these contracts is still emerging. Despite favorable legislation for innovative public contracting, evidence points to limited application of this approach. The study concludes that while there is a generally positive perception of promoting innovation in public procurement, and efforts have been made, significant challenges remain. Chief among these are fostering a culture of innovation within public institutions, ensuring public agents are trained and equipped to implement and manage innovative processes, and strengthening collaboration between managers and control bodies to ensure legal compliance in implementing innovations.